Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2003
DOI: 10.1046/j.1365-2702.2003.00644.x
|View full text |Cite
|
Sign up to set email alerts
|

Health care workers' action strategies in situations that involve a risk of blood exposure

Abstract: Previous research shows that health care workers (HCWs) often act in a risky way in blood-exposure situations, and thereby run the risk of becoming infected by blood-borne pathogens. A qualitative study was conducted in order to describe factors that influence HCWs' actions in such situations. Nurses and nursing assistants were interviewed. The analysis shows that HCWs perceive that there is a conflict among different demands. These demands are protecting the patient's privacy, protecting themselves from being… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0
1

Year Published

2004
2004
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 12 publications
1
10
0
1
Order By: Relevance
“…We also referred to these forces as deactivators. These have been more thoroughly discussed in a previous article (Lymer et al. , 2003).…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…We also referred to these forces as deactivators. These have been more thoroughly discussed in a previous article (Lymer et al. , 2003).…”
Section: Discussionmentioning
confidence: 95%
“…In a previous article (Lymer et al. , 2003), we argued that a qualitative approach is needed to complement the existing research.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies of hospital health care workers have found that provision of other resources (such as training), structural factors (such as work loads), and workers' perceptions of management's commitment to worker safety have a strong effect on compliance with Universal Precautions, use of safety devices, and risk of blood exposure [17][18][19][20] . Intervention strategies for paramedics should take into account the complex relationships of organizational, structural, and psychosocial factors that affect blood exposure 15,21) .…”
Section: Resultsmentioning
confidence: 99%
“…Williams et al (1994) identificaram que 57% dos trabalhadores que indicaram uma baixa adesão às precauções-padrão referiram esta atitude ao fato do paciente não ter aparência de ser um portador de vírus passível de transmissão ocupacional. Em uma investigação qualitativa sobre o uso de luvas na punção venosa, Zapparoli (2005) observou que em 35% dos depoimentos foi referido o uso de luvas apenas quando era conhecido que o diagnóstico do paciente representava risco de contaminação Todo trabalhador de saúde deve partir do pressuposto de que todos os pacientes podem estar infectados por patógenos passíveis de transmissão de infecções e outras patologias e adotar as precauções-padrão (LYMER, RICHT, ISAKSSON, 2003).…”
Section: Aplicação Da Ferramenta De Treinamentounclassified